Transferring variable costs reduction to prices to take advantage of idle capacity (Costos y Gestión, 2021)
The article studies the cases of poly-production companies with common restrictors that are operating inoptimal market conditions with wasted productive and / or commercial capacity, focusing on variable costoptimization projects that allow a proportion of the reduction obtained to be transferred to price, in search ofthe triple objective: maximization of market share, maximization of profits and use of idle capacity. It is part of the development of quadratic models for optimizing prices and product mixes in the face ofrestrictions in contexts of competitive markets, where income functions have a non-linear behavior due to theneed to reduce price to increase the volume of sales, considering price-demand elasticity as a relevant variableof the model. The modeling is presented at a theoretical and practical level, supported by a spreadsheet withwidely used non-linear operational research functions.
Keywords: Elasticity; Pricing; Non-linear operational research; Idle capacity; Market share